THE TAXATION OF CO-OPERATIVES’ INCOME: ANALYSIS OF ITS RATIONALE - Aguiar, Nina (International Journal of Cooperative Law, 2025)
In this paper we address the issue of taxation of cooperatives’ income. Cooperatives traditionallyreceive a specific tax treatment distinct from that given to companies. In general terms, thatspecific cooperative tax regime is apparently more favorable when compared to the one applied to companies. A tradition of granting cooperatives a favorable taxrelief-based tax regime is widely extended, being noticeable inall Western European Countriesandin the Northern American countries (USA and Canada). This paper seeks to lay down some conceptual basis on which the issue ought to beanalyzed, with aspecial emphasis on the definition of what is to be treated as cooperative income for tax purposes and the rationale for afavorable cooperative tax regime.